2006
DOI: 10.1159/000103583
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Sonic Hedgehog Signaling Affects Axon Routing in the Mouse Optic Chiasm

Abstract: The morphogen Sonic hedgehog (Shh) has recently been shown as an axon guidance molecule in the development of central neural pathways. We investigated here whether Shh serves its axon guidance role in patterning axon course in the mouse optic chiasm. Using immunocytochemistry, Shh-like staining was observed in the caudal regions of the ventral diencephalon in embryonic day (E) 13 embryos. At E14 and E15, the staining became obvious on the optic axons in lateral regions of the chiasm and in the optic tract, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Here, we provide the first evidence that Shh plays a role in retinal pathfinding at distal regions of the developing visual system in Xenopus. First, our expression studies show that Xshh mRNA is distributed in a pattern quite similar to that reported for chick and mouse at the optic chiasm, with strong expression on either side of the route taken by RGC axons as they cross the ventral midline (Trousse et al, 2001;Hao et al, 2007). This spatiotemporal expression pattern suggests that Xenopus RGC axons, like those of chicks and mice, use a conserved mechanism, where Shh is a chemorepellent that guides retinal axons at the optic chiasm during contralateral wiring of the visual system.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Here, we provide the first evidence that Shh plays a role in retinal pathfinding at distal regions of the developing visual system in Xenopus. First, our expression studies show that Xshh mRNA is distributed in a pattern quite similar to that reported for chick and mouse at the optic chiasm, with strong expression on either side of the route taken by RGC axons as they cross the ventral midline (Trousse et al, 2001;Hao et al, 2007). This spatiotemporal expression pattern suggests that Xenopus RGC axons, like those of chicks and mice, use a conserved mechanism, where Shh is a chemorepellent that guides retinal axons at the optic chiasm during contralateral wiring of the visual system.…”
Section: Discussionsupporting
confidence: 75%
“…In chicks, Shh is important for pathfinding within the retina (Kolpak et al, 2005) and at the optic chiasm (Trousse et al, 2001). In mice, Shh functions during intraretinal RGC extension (Sanchez-Camacho and Bovolenta, 2008), and in guidance at the optic chiasm (Hao et al, 2007;Sanchez-Camacho and Bovolenta, 2008). Shh is also used by commissural axons of the mouse spinal cord, to promote midline axon guidance, in conjunction with Netrin-1 (Charron et al, 2003) and through Boc receptors (Okada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the developing embryo, there are a number of guidance cues that are expressed in the brain in a highly organized spatial and temporal fashion to ensure that developing RGC axons project correctly through the optic chiasm and toward their central targets. Axon-guidance molecules include neutrins, semaphorins, laminin, multiple members of the Ephrin/Eph families, glial markers, slits, and chondroitin sulfate proteoglycan molecules 1638. Pair box–containing gene, Pax2, is an essential guidance cue during embryogenesis and is expressed by astroglia in the optic nerve throughout development to form a growth promoting corridor to guide newly developing RGC axons along the optic nerve towards the developing optic chiasm 16,39–43…”
mentioning
confidence: 99%
“…The glial markers radial glial cell marker 2 (RC2), brain lipid binding protein (BLBP) and slit guidance ligand 1 (Slit1) have been identified in the area surrounding the embryonic optic chiasm and are usually described as inhibitory guidance cues. It is believed these inhibitors assist in directing newly formed RGC axons towards the optic tracts in both sides of the brain, thus avoiding misguidance into surrounding tissue 16,18,1921,23,27,3336,4446. Slit1 in particular restricts RGC axons extending outside the optic chiasm whilst BLBP and RC2 positive radial glia, located immediately posterior to the murine optic chiasm,20,32,46,47 possess short end-feet projections that interact with and guide retinal axons through the chiasm.…”
mentioning
confidence: 99%
“…Moreover, Chan SunOn and colleagues found that the morphogen sonic hedgehog (Shh) protein, which has been shown to guide the midline crossing of commissural axons in the spinal cord [31], may also guide the pathfinding of retinofugal projections in mice at different developmental stages [32][33][34]. They observed that Shh is localized largely in the lateral regions of the chiasm and at the optic tract, and to a lesser extent in the caudal regions of the diencephalon.…”
Section: Guidance Of Retinal Axons In the Optic Chiasm By Other Proteinsmentioning
confidence: 99%